The Bacterial Spore 2016
DOI: 10.1128/9781555819323.ch1
|View full text |Cite
|
Sign up to set email alerts
|

Genome Diversity of Spore-Forming Firmicutes

Abstract: Formation of heat-resistant endospores is a specific property of the members of the phylum Firmicutes (low-G+C Gram-positive bacteria). It is found in representatives of four different classes of Firmicutes: Bacilli, Clostridia, Erysipelotrichia, and Negativicutes, which all encode similar sets of core sporulation proteins. Each of these classes also includes non-spore-forming organisms that sometimes belong to the same genus or even species as their spore-forming relatives. This chapter reviews the diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 136 publications
5
49
0
1
Order By: Relevance
“…This scenario does not explain rRNA decay in Megavirales as compared with mitochondrial rRNA and the apparent independent origin of mitochondrial proteins. 68 The scenario suggests that similarities between giant viruses and bacterial endospores (these protein-coated forms enable bacteria to survive extreme conditions 70 and apparently evolved independently in different bacterial lineages [71][72][73] ), which are usually seen as analogies, 44,74 indicate common ancestry. Mitochondrial budding 54 also fits this hypothesis.…”
Section: Synteny Between the Genomes Of Megavirales And Amoeban Mitocmentioning
confidence: 99%
“…This scenario does not explain rRNA decay in Megavirales as compared with mitochondrial rRNA and the apparent independent origin of mitochondrial proteins. 68 The scenario suggests that similarities between giant viruses and bacterial endospores (these protein-coated forms enable bacteria to survive extreme conditions 70 and apparently evolved independently in different bacterial lineages [71][72][73] ), which are usually seen as analogies, 44,74 indicate common ancestry. Mitochondrial budding 54 also fits this hypothesis.…”
Section: Synteny Between the Genomes Of Megavirales And Amoeban Mitocmentioning
confidence: 99%
“…The entire complex may then have been co-opted by the phosphorelay to regulate it in response to the redox state. As bacteria moved into more stable niches, with steady nutrient supplies and less changeable environments, sporulation was lost, along with most of the genes associated with sporulation (Galperin, 2013). Although the phosphorelay and Spo0A disappeared, the ric genes were not immediately lost, persisting in the non- rRNA sequences from the RDP database rooted to the outgroup Streptomyces fradiae as described in Experimental Procedures (Cole et al, 2009).…”
Section: Enhancement Of the Phosphorelay Is Not The Only Function Of mentioning
confidence: 99%
“…For example, in nutrient-rich environments after 6,000 generations of B. subtilis, neutral processes but also selection were found to facilitate loss of sporulation (Maughan et al 2007), occurring by indels or single-nucleotide substitutions (Maughan et al 2009). In nature though, sporulation loss is mostly driven by consecutive gene losses as suggested earlier (Galperin et al 2012;Galperin 2013) and demonstrated in (Abecasis et al 2013) while Caldicellulosiruptor species have between 62.5 and 73%, so there is still some speculation as to whether the latter form spores or not (Abecasis et al 2013). The same question has persisted for sometime for Ruminococcus species (Galperin et al 2012;Abecasis et al 2013).…”
Section: Discussionmentioning
confidence: 86%
“…Still, they were recently shown to sporulate (Browne et al 2016;Mukhopadhya et al 2018), and are likely to spread as spore-like structures between hosts (Schloss et al 2014;Mukhopadhya et al 2018), which plays as a counter evolutionary force to the emergence of asporogenous phenotypes. In other cases, notably Epulopiscium and Candidatus Arthromitus, sporulation has evolved as a reproductive mechanism, involving some gene loss ( Figure 3B) and eventually the gain of new genes (Flint et al 2005;Galperin 2013), under distinct evolutionary forces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation